Medical and psychological support and psycho-physiological examination of extreme activities specialists - A. V. Starkov; V. V. Yusupov; B. V. Ovchinnikov; V. A. Korzunin; P. A. Porozhnikov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The essence of medical and psychological support is a continuous monitoring of functional and mental state of specialists and the system of mental health interventions aimed at maintaining the optimal level of occupational performance. The scientific basis of this direction is the idea of an integrated system of professional psychological and physiological adaptation in normal conditions, in condition of pre-pathology and pathology. Psychophysiological (professional and psychological) examination of specialists is an integral part of medical and psychological support, and presents a set of measures aimed at in-depth study of individual psychological characteristics of personality and evaluation of the specialists' organism functional reserves in the process of their occupational duties implementation to determine the conformity of their professionally important qualities to the requirements of specific occupational activity.